Assessment of thyroid hormone assays. Issue 12 (December 1976) - Evered, D C; Vice, P A; Green, E; Appleton, D
Abstract : Four techniques for estimating serum T4 and three for estimating serum T3 have been investigated and found to be satisfactory in routine use. Normal ranges for each techniques have been established. Estimation of serum T3 by the commerical kits tested appears to have a high discriminant value in the diagnosis of hyperthyroidism, although the diagnostic definition used inevitably enhances the apparent sensitivity of these techniques. Estimation of serum T4 will identify the majority of patients with symptomatic hypothyroidism. The low sensitivity of T3 in the diagnosis of thyroid failure is confirmed.